Integrasi Kecerdasan Buatan dalam Pendidikan Karakter: Menjembatani Kesenjangan Digital untuk Generasi Z - Parjana, Cepi (Andragogia: Journal Education Science And Islamic Studies, 2025)
The technological revolution has transformed many aspects of human life, including how we educate younger generations. Generation Z, raised amidst the digital era, faces unique challenges and opportunities unlike any previous generation. In an increasingly interconnected world, character education is pivotal to guiding them through the complexities of modern life with strong moral values. Integrating artificial intelligence (AI) into character education paves the way for innovative approaches that adapt to contemporary needs. This journal explores the role of AI in fostering character development in Generation Z, providing theoretical insights, global case studies, and practical strategies to bridge traditional character education with rapid technological advancements. Through literature review methodology, this study examines the benefits, challenges, and implications of AI integration in character education, aiming to provide a framework for educators and policymakers to adapt character education to the needs of the digital age.